Political connections and the SEC confidential treatment process - Thompson, Anne M. (Journal of Accounting and Economics, 2022)
SEC confidential treatment (CT) orders are regulatory exemptions that enable firms to redact proprietary information from SEC filings if the disclosure would cause competitive harm and if the information is immaterial to investors. This study examines the role of firms' political connections in the SEC's decisions to approve versus reject CT requests before and after Congressional intervention and internal SEC scrutiny into the CT process. CT requests from politically connected firms are less likely to be rejected before Congressional intervention and internal SEC scrutiny and are more likely to be rejected following these events. When the SEC rejects CT requests, firms must disclose the contents of the unapproved redactions. These disclosures are informative to investors, on average, and are less informative following Congressional intervention and internal SEC scrutiny. Together, these findings contribute to the literature on political influence in SEC oversight and disclosure regulation and provide unique evidence on the role of Congressional intervention in SEC decision making.